Subpopulation dynamics of T and B lymphocytes in Sjögren’s syndrome: implications for disease activity and treatment - Meng, Qingliang; Ma, Junfu; Cui, Jiakang; Gu, Yangyi; Shan, Yu (Frontiers in Immunology, 2024)
Sjögren's syndrome (SS) is an autoimmune disorder primarily affecting the body's exocrine glands, particularly the salivary and lacrimal glands, which lead to severe symptoms of dry eyes and mouth. The pathogenesis of SS involves the production of autoantibodies by activated immune cells, and secretion of multiple cytokines, which collectively lead to tissue damage and functional impairment. In SS, the Immune interaction among T and B cells is particularly significant. Lymphocytic infiltration in the salivary glands is predominantly composed of CD4+ T cells, whose activation cause the death of glandular epithelial cells and subsequent tissue destruction. The excessive activity of T cells contributes significantly to the disease mechanism, with helper T cells (CD4+) differentiating into various subgroups including Th1/Th2, Th17, as well as Treg, each contributing to the pathological process through distinct cytokine secretion. In patients with SS, B cells are excessively activated, leading to substantial production of autoantibodies. These antibodies can attack self-tissues, especially the lacrimal and salivary glands, causing inflammation and tissue damage. Changes in B cell subpopulations in SS patients, such as increases in plasmablasts and plasma cells, correlate positively with serum autoantibody levels and disease progression. Therapies targeting T cells and B cells are extensively researched with the aim of alleviating symptoms and improving the quality of life for patients. Understanding how these cells promote disease development through various mechanisms, and further identifying novel T and B cell subgroups with functional characterization, will facilitate the development of more effective strategies to treat SS.